Ivy league universities facing tough competition - Abd Razak, Dzulkifli (2008)
TRANSFORMATION is rightly about creating a better future for achieving new successes. The past, no matter how successful, can never guarantee future successes, especially in everchanging tunes when successes at best are often momentary in nature. Their halflives are getting shorter and shorter each time, more so when it comes to knowledge creation and generated outcomes. This has serious implications for universities, where knowledge is created and generated, the world over. Even the more established "worldclass" universities can no longer be assured of the many successes if they choose to focus on just what they are good at.